Promoting nurses mental health - Marie Poggenpoel (AOSIS, 1996)
In this article obstacles that influence nurses mental health are described as well as ways to address the obstacles to promote mental health. Opsomming In hierdie artikel word struikelblokke wat verpleegkundiges se geestesgesondheid beinvloed beskryf asook wyses hoe om die struikelblokke aan te spreek om sodoende geestesgesondheid te bevorder. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.